Reproductive attributes of the spot-tail shark, Carcharhinus sorrah collected from westernmost waters of Aceh, Indonesia - Teuku Haris Iqbal; Ilham Fajri; Adrian Damora; Ahmad Fauzan Lubis; Benaya Meitasari Simeon; Efin Muttaqin; Hollie Booth (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
The spot-tail shark, Carcharhinus sorrah is a species of requiem shark found primarily in warm coastal waters of the Indo-Pacific region. This study aims to assess the length at first maturity and length distribution The spot-tail shark, C. sorrah collected from key fish landing sites in Aceh Province, Indonesia. Data collection occurred between March 2020 and October 2022 at three fishing ports: Banda Aceh (BA), Aceh Barat (AB), and Aceh Barat Daya (ABD). A One-way Analysis of Variance (ANOVA) was employed to analyze the total length (TL) of male and female fish from these sites. Results indicated an overall sex ratio of female to male fish at 1:1.67 ( = 45.19, p 0.001), with significant differences observed in sex ratios between BA and ABD ( = 6.72, p = 0.01; = 41.14, p 0.001), while AB showed no significant difference ( = 1.64, p = 0.20). Logistic regression analysis revealed variations in the length at which 50% of males and females reached maturity (Lm50): males from ABD, AB, and BA were 110.65 cm TL, 117.03 cm TL, and 152.65 cm TL, respectively, while females from BA, ABD, and AB were 107.30 cm TL, 113.94 cm TL, and 116.14 cm TL, respectively. Notably, males from ABD and females from BA matured earlier than those from other sites. In terms of length distribution, the average greatest with standard deviation (SD) length of male C. sorrah was 122.8737.87 cm TL in AB, followed by BA at 113.8013.10 cm TL and ABD at 107.8618.38 cm TL. This species is important for both ecological balance and fisheries, emphasizing the need for effective management and conservation efforts.Keywords:The spot-tail sharkCarcharhinus sorrahsex ratiolength at first maturitywesternmost Indonesia